Increasing leaf vein density via mutagenesis in rice results in an enhanced rate of photosynthesis, smaller cell sizes and can reduce interveinal mesophyll cell number - Feldman, Aryo B.; Leung, Hei; Baraoidan, Marietta; Elmido-Mabilangan, Abigail; Canicosa, Irma; Quick, William P.; Sheehy, John; Murchie, Erik H. (Frontiers Media, 2017)
Improvements to leaf photosynthetic rates of crops can be achieved by targeted manipulation of individual component processes, such as the activity and properties of RuBisCO or photoprotection. This study shows that simple forward genetic screens of mutant populations can also be used to rapidly generate photosynthesis variants that are useful for breeding. Increasing leaf vein density (concentration of vascular tissue per unit leaf area) has important implications for plant hydraulic properties and assimilate transport. It was an important step to improving photosynthetic rates in the evolution of both C3 and C4 species and is a foundation or prerequisite trait for C4 engineering in crops like rice (Oryza sativa). A previous high throughput screen identified five mutant rice lines (cv. IR64) with increased vein densities and associated narrower leaf widths (Feldman et al., 2014). Here, these high vein density rice variants were analyzed for properties related to photosynthesis. Two lines were identified as having significantly reduced mesophyll to bundle sheath cell number ratios. All five lines had 20% higher light saturated photosynthetic capacity per unit leaf area, higher maximum carboxylation rates, dark respiration rates and electron transport capacities. This was associated with no significant differences in leaf thickness, stomatal conductance or CO2 compensation point between mutants and the wild-type. The enhanced photosynthetic rate in these lines may be a result of increased RuBisCO and electron transport component amount and/or activity and/or enhanced transport of photoassimilates. We conclude that high vein density (associated with altered mesophyll cell length and number) is a trait that may confer increased photosynthetic efficiency without increased transpiration.